NILAI-NILAI ISLAM DALAM KONSTRUKSI SOSIAL KONSERVASI LINGKUNGAN PESISIR (STUDI DI MANGROVE CENTERTUBAN) - Fandi Sudiasmo (Universitas Muhammadiyah Malang, 2017)
Various problems related to the growth of coastel area are rapidly relative, definitely the handling steps immediately should be concepted. In addition of what have been predicted, in this time one demage of the coastel area is demaged of mangrove, so that why the conservation in coastel area extremely needed because there are several benefits for society. Mangrove Center of Tuban (MCT) is one of institute that has been developing the conservation of coastel area. The purpose in this research is understanding the values of Islam in social construction of coastel area conservation in Tuban Mangroves Center, utilised the qualitative research with phenomenological approach, use the analysis techniques of research phenomenological Creswell data, did in Jenu village- Jenu subdistricts regency of Tuban. The existency of conservation activities surely not released to the process of social construction. The concept of social construction is the meaning of each individul process for each areas and each outside aspect consist of Externalitation process,Objectivation, and internalitation. Start from the activities, planting of mangrove that planted everyday, be a habits, have an institute other socialitation to make some conservations. Conservation activities as a realization of values in religion (Islam), pay attention to some areas not liberated from the verses of the holy Qur’an (QS Al Isra (17): 44).